Der Streit um Christa Wolf : eine Untersuchung ihrer Rolle als Geheimer Informator der Stasi, als Mittelpunkt des Literaturstreits und als Autorin des Romans, Der geteilte Himmel : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in German at Massey University - McGhie, Judith Karen (Massey University, 1997)
1990 saw the beginning of the 'Literaturstreit' (the Literary Controversy) in East and West Germany. The 'Literaturstreit' was sparked off by the publication of Christa Wolf's short narrative Was bleibt in June 1990. Wolf's insistence that the narrative had been written back in 1979, when she was under Stasi surveillance, and that she had revised it in 1989 prior to publication, brought a barrage of criticism from prominent critics from all over the world. The 'Literaturstreit' was further fired by the publication of the Stasi files in 1993, which revealed Christa Wolf's involvement with the Stasi. In the first part of this thesis the Stasi files are investigated in order to determine the nature of the information given to the Stasi by Christa Wolf and to establish her actual involvement with them. In order to establish a picture of her character at the time in which she was recruited by the Stasi, the first chapter examines two curricula vitae written by herself and letters, reports and assessments regarding Christa Wolf written by colleagues and Stasi agents. The second chapter takes a close look at the actual process used by the Stasi to recruit Wolf as a "Secret Informer". It is my intention in the second part of this thesis to compare the picture of Christa Wolf seen in the Stasi files with the picture of her established in her narrative Der geteilte Himmel and with the picture of her which emerges through the criticisms levelled at her during the 'Literaturstreit'. Chapter Three outlines the major issues of the 'Literaturstreit' and events leading to it and summarizes the main critical arguments against Christa Wolf during this time. The focus of chapter Four is an examination of Christa Wolf's novel Der geteilte Himmel. published in 1963. The reason behind the choice of this novel is that it is the literary work which was published shortly after Christa Wolfs involvement with the Stasi and was presumably written - at least in part - while she was still officially in their employ. It is concluded that Christa Wolf is not the naive or self-consumed person portrayed in the Stasi files who is afraid to express her beliefs and make judgements. She appears to have felt obliged to work for the Stasi due to the position that she held at the time, but she may also have seen it as an opportunity for her to gain insight into the real situation in the party and in its institutions. The comparison between the Christa Wolf as portrayed in the Stasi files, the Christa Wolf as seen by the critics in the 'Literaturstreit' and the Christa Wolf who expresses herself through the literary text is revealing. However, despite the differences - legitimate or otherwise - that emerge, her faith in the real values of true Socialism remains constant.
Keywords: Wolf, Christa; Political and social views